The Influence of Self-Efficacy and Entrepreneurial Skills Towards the Readiness of Entrepreneurial Students in the Era of Society 5.0 - Anna Marganingsih; Angselmus Dendi; Emilia Dewiwati Pelipa; Dessy Triana Relita; Munawar Thoharudin (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
This study aims to determine self-efficacy and entrepreneurial skills on student entrepreneurship readiness in the era of society 5.0 at STKIP Persada Khatulistiwa Sintang, and the effect of self-efficacy and entrepreneurial skills on student entrepreneurial readiness at STKIP Persada Khatulistiwa Sintang. The method used in this research is quantitative and the form of the research is multiple linear regression research. The population in this study were 329 students of STKIP Persada Kahatulistiwa Sintang with a total sample of 76 students. Sampling technique with random sampling. The data collection technique used was a questionnaire. Data processing in research uses EXCEL and SPSS 26 with data processing techniques using validity tests, linearity tests, classical assumption tests, contribution tests and hypothesis testing. The results showed that self-efficacy and entrepreneurship skills partially had a significant influence on student entrepreneurship readiness. This was shown by the t-count self-efficacy (X1) 0.000 <0.05 and t-count entrepreneurship skills (X2) 0.000 <0.05. Self-efficacy and entrepreneurial skills simultaneously have a significant effect on student readiness for entrepreneurship, this is indicated by a sig value of 0.000 < a sig level value of 0.05 and an F count of 170.065 >. Among the self-efficacy and entrepreneurship skills that have the most dominant influence on student entrepreneurship readiness is variable X2 (entrepreneurship skills) because it has a higher coefficient of 0.616 compared to variable X1 (self-efficacy) with a coefficient value of 0.294. Based on the results of the study, it can be concluded that Self-Efficacy and Entrepreneurial Skills affect the Entrepreneurial Readiness of Students in the Soceity 5.0 Era at STKIP Persada Khatulistiwa Sintang